Implementing Cartoon Media to Maximise Students’ Reading Comprehension - Widya Rahmawati; Sandi Yusuf (Universitas Ahmad Dahlan, 2020)
The objectives of this research are to find out whether there is a significant difference in the reading comprehension between students who are taught by using cartoon media and the students who are taught by using conventional media, to find out the effectiveness between cartoon media and conventional media in teaching reading comprehension. This experimental research was carried out in SMP Muhammadiyah 1 Sleman in the academic year of 2018/2019. The findings of the study show that the mean scores of students who were taught by using cartoon media are higher than the scores of those who were taught by using conventional media, 68.16 > 60.91. The result of ANCOVA shows the level of significance is lower than 0.05. i.e. 0.0000 < 0.05. thus H1is accepted and Ho is rejected. It shows clearly that the use of cartoon media to teach reading comprehension is more effective than conventional media.